Failure mechanisms of sandstone subjected to cyclic loading considering stress amplitude effects - Qican Ran; Yunpei Liang; Quanle Zou; Zihan Chen; Jinfei Zhan; Liang Chen; Zhaopeng Wu; Tengfei Ma (International Journal of Coal Science & Technology)
Abstract In underground engineering fields, such as mining engineering, rocks are often subjected to cyclic loading, resulting in the deterioration of their mechanical properties, which poses a serious threat to engineering construction. Thus, investigating the mechanical response of rocks under cyclic loading is meaningful. Cyclic loading experiments were conducted on sandstone samples with different cyclic stress amplitudes (CSAs). First, the deformation characteristics and strain energy evolution were analyzed. The internal fracture extension and fragmentation characteristics of sandstone after failure were subsequently analyzed. Finally, the failure mechanism of sandstone was investigated. The results revealed that deformation, failure mode, and particle fragmentation characteristics were affected by the CSA, with the peak strain being greatest in sandstone samples subjected to the greatest CSA. With increasing CSA, the load‒unload response ratio of sandstone under the last cyclic stage generally tends to increase. Furthermore, there was an increasing trend in the dissipated energy percentage of sandstone as the CSA increased, which was a result of the increased energy used to drive fracture extension. Moreover, the sandstone exhibited a tensile‒shear composite failure mode dominated by shear failure. Nevertheless, with increasing CSA, the shear failure surface became more obvious. In addition, the proportion of small blocks and the fragmentation fractal dimension increased as the CSA increased, which indicated a high degree of fragmentation. Additionally, a sandstone damage constitutive model was developed to describe the results. Eventually, the macro–meso failure mechanism of sandstone considering CSA effects was revealed. Under high CSA, the internal fracture extension and particle friction of sandstone increased, which is the internal cause. The mechanical parameters indicated strong deformation and high dissipated energy characteristics, which is the external manifestation. This investigation is important for preventing the occurrence of disasters in underground engineering, such as coal mining.